2021
DOI: 10.1177/2278533721994712
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Job Satisfaction on Turnover Intentions and Job Mismatch Among Millennial Employees in Bengaluru

Abstract: The millennials have become the largest cohort in the workforce, and their retention has become challenging for policymakers and organizations. Millennials are career-oriented and are ready to switch jobs if there is a mismatch in skills and job requirement. The purpose of this study is to investigate the mediating role of job satisfaction on turnover intention and job mismatch among millennial employees in Bengaluru. The study consists of 247 millennial employees from different industries of Bengaluru. Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…Extant literature regarding the relation between work factors and employee turnover is mainly based on Herzberg’s two-factor theory, person-job matching theory and other traditional theories (Chavadi et al, 2021). However, the current study revealed that decent work negatively affected millennial employees’ withdrawal intentions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant literature regarding the relation between work factors and employee turnover is mainly based on Herzberg’s two-factor theory, person-job matching theory and other traditional theories (Chavadi et al, 2021). However, the current study revealed that decent work negatively affected millennial employees’ withdrawal intentions.…”
Section: Discussionmentioning
confidence: 99%
“…The following recommendations are proposed based on the study’s findings. First, in the world of work, interventions aimed at lowering turnover mainly focus on job satisfaction (Chavadi et al, 2021; Lee et al, 2017) and job embeddedness (Hassan et al, 2021; Orie & Semejin, 2021). But our findings highlight the key role that overall well-being may play in turnover intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lee et al (2017) showed that job satisfaction of early-career employees exerts a negative impact on their turnover intention. A recent study on millennial employees in India also found that job satisfaction was negatively correlated with turnover intention (Chavadi et al, 2021). Thus, the following hypothesis is proposed:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 98%
“…Firstly, studies have demonstrated the high turnover of new generation employees as a pressing issue in many organizations all around the world and have called for more research to address it (Chavadi et al, 2021). Previous studies have focused on the influence of organization support (Cheng & Lin, 2017), inclusive talent development model (Fang et al, 2020), and job mismatch (Chavadi et al, 2021) Secondly, our theoretical model not only explains how decent work is linked to the turnover intention of new generation employees but also explores job satisfaction as an underlying mechanism in this relationship. A review of the literature reveals that although past studies have explored the outcomes of decent work (Chen et al, 2020;McIlveen et al, 2021), little attention has been paid to the underlying reasons behind the relationship between decent work and turnover intention in organizational contexts.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…It has been well-documented that a growing number of organizations are requiring managers, along with regular duties and responsibilities, to engage in coaching employees primarily to create performance improvement along with positive manager–employee relationships (Lawrence, 2017; DiGirolamo and Tkach, 2019). And, the improvements in work and relationships are also expected to aid in retention of valued employees (Chavadi, et al , 2021). Some organizations provide training in coaching practice to include use of learning/instructional tools.…”
Section: Introductionmentioning
confidence: 99%